Student growth, qualities, and abilities in developing religious ideals from childhood. Which approach works? - Pandia, Weny Safitri S.; Naim, M. Ainun; Siddique, Muhammad (Assyfa Journal of Islamic Studies, 2023)
It is well recognized that introducing religious principles during early life is crucial as it has the potential to impact and mould a child's perception of truth. Children possess the capacity to engage in two distinct cognitive processes when considering matters of morality and truth, which vary depending on the level of the child's developmental maturity. The purpose of this article is to delineate the process of imparting religious principles during early life, both within the family setting and early childhood education institutions. The study employed a descriptive qualitative methodology, which involved reviewing pertinent literature from the past decade (2013-2023), including theses, dissertations, and papers indexed by SINTA or Scopus. The research data consists of excerpts extracted from sentences found in diverse literature, which depict the incorporation of religious beliefs during early life. The data was acquired through the utilization of reading and note-taking methodologies. After being gathered, the data was examined using descriptive methodologies. The study's findings indicate that prior research on the introduction of religious ideals throughout early life has reported inconsistent results. Typically, young children are taught Aqidah principles, religious values, and moral standards that are tailored to their growth, traits, and capabilities. These religious ideals are imparted through the means of exemplification, habituation, parables, storytelling, and discourse.